Methylene Blue to the Rescue in Accidental Treprostinil Overdose - Sundaravel, Swethika; Asaweer, Majid; Stoller, Douglas; Chatzizisis, Ioannis; Zolty, Ronald (Cardiology and Cardiovascular Medicine, 2020)
The incidence of pulmonary hypertension (PH) has been rising enormously over the past few years, with more systemic diseases being found to be associated with it. A better understanding of the pathophysiology of PH has led to the development of more effective therapies that have impacted the survival and morbidity of these patients. However, the adverse effects associated with these medical therapies are often serious and not trivial. Here we present a case of an inadvertent overdose of oral treprostinil diolamine that led to refractory vasoplegic shock.